RANCANGAN PEMBANGUNAN HUTAN RAKYAT DI INDONESIA - Fransiskus Xaverius Dako (Politeknik Pertanian Negeri Kupang, 2012)
Masterplan of Community Forest Development in Indonesia. Community forest is a forest area which owned by people with a minimum of 0.25 ha with a canopy of woody plants and/or other plant species more than 50 % and/or in the first year with plants of at least 500 plants per hectare.The main purpose of development community forests are to increase the productivity of marginal lands, helping the diversify of agricultural products who needed by society, prepare of timber and building materials industries as well as fire wood, increasing farmers’s in come in rural communities and enhancing their welfare, also improve the water system and the environment specially on land belongs to the people who are in the up stream waters hield protection areas. Forest development program hopefully not only produce of woods but also produce the other commodities and services, such as foods, fodders, medicines,etc. which considered a balance of ecology, social and economy. The development of community forests can also support and provide solutions in forestry problems with the way recovery the forests which transformed into shrubs and weeds, also change people's behavior by providing jobs for the community. With the development of community forests can support the availability of job for the community which impact on income for them.Key words: development, forest, community